YouTube™ as a source of information on prostatitis: a quality and reliability analysis - ÖZGÜR, EMRAH GÖKAY (My University, 2023)
It was aimed to analyze the YouTube™ videos on prostatitis regarding their source, content, and information included. The term “prostatitis” was searched by relevance and the first 200 video links and features were recorded. Using the 5-point modified DISCERN tool, Global Quality Score (GQS), and Journal of American Medical Association (JAMA) score, the quality and reliability of the information were assessed by two urologists. Inter-rater agreement for DISCERN, JAMA, and GQS had Cohen’s kappa coefficients of 0.883, 0.887, and 0.885, respectively. The most common source of upload was doctors/medical institutions (33.0%), and the majority of the content was about general information (27.0%). The mean modified DISCERN, GQS and JAMA scores were 3.24 ± 1.23 (1.00–5.00), 3.25 ± 1.26 (1.00–5.00) and 2.17 ± 1.36 (0.00–4.00), respectively. These scores were correlated with each other (r = 0.914, p < 0.001 between JAMA and GQS; r = 0.954, p < 0.001 between JAMA and modified DISCERN; and r = 0.885, p < 0.001 between GQS and modified DISCERN, Spearman test) and were the highest in the videos uploaded by doctors/medical institutions (p < 0.001, Kruskal-Wallis test). Of the videos, 25.5% were poor, 30.5% were moderate and 44.0% were high quality. The high quality videos were significantly shorter than those with poor quality (p = 0.039, Kruskal-Wallis test). The poor quality videos had the highest view ratio (50.49 ± 127.74 (0.03–618.91), p = 0.036, Kruskal-Wallis test). Most YouTube™ videos on prostatitis are short and high quality videos uploaded by doctors/medical institutions. However, these videos have less view ratios than those with poor quality.